Exchange of Information and Expertise 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Association for Farming Systems Research Extension (AFSRE), Los Banos, Philippines: 'We have been receiving numerous requests for free publication, the Journal and Newsletter and all other information, citing Spore as their source of information...